Factors affecting maximal oxygen uptake in prepubertal children: a systematic review and meta-analysis - Iva Jurov; Jure Demšar (BMC, 2024)
Abstract In pre-pubertal children the factors affecting maximal oxygen uptake have yet to be fully understood. Therefore, the purpose of this analysis is to present cardiorespiratory fitness in prepubertal boys and girls and to determine if there are any differences based on sex, exercise testing modality or if maximal or peak oxygen consumption metrics are used. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed. For statistical analysis, multilevel models grounded in Bayesian principles were used. Selected studies obtained: maximal effort during the test, peak or maximal oxygen consumption (V̇O2) values, boys and girls (sex specific groups only) age under 11, cycle ergometry or treadmill, pre-intervention or no intervention data. In boys using cycle ergometry, 118 studies were included in the analysis, in boys using treadmill 115, in girls using cycle ergometry 83 and in girls using treadmill testing 95 study entries were included. As children get older, their cardiorespiratory fitness increases (P ≈ 100%). Studies with participants having smaller body mass have higher V̇O2 relative to body mass values (P ≈ 100%). Boys have higher V̇O2 values than girls (P ≈ 100%). Studies using treadmill reported higher values than those using cycle ergometer (P ≈ 100%). Regarding the influence of measurement method (max vs. peak) on V̇O2 values we did not find significant differences. In conclusion, we present reference values for cardiorespiratory fitness in prepubertal boys and girls using cycle ergometry or treadmill. Prepubertal boys have higher cardiorespiratory fitness than girls and using treadmill testing might be a preferred method to cycle ergometry, especially in older children. Maximal or peak oxygen consumption metrics might be used interchangeably in prepubertal children.